Memory Impedance in TiO(2) based Metal-Insulator-Metal Devices - Qingjiang, Li (Nature Publishing Group, 2014)
Large attention has recently been given to a novel technology named memristor, for having the potential of becoming the new electronic device standard. Yet, its manifestation as the fourth missing element is rather controversial among scientists. Here we demonstrate that TiO(2)-based metal-insulator-metal devices are more than just a memory-resistor. They possess resistive, capacitive and inductive components that can concurrently be programmed; essentially exhibiting a convolution of memristive, memcapacitive and meminductive effects. We show how non-zero crossing current-voltage hysteresis loops can appear and we experimentally demonstrate their frequency response as memcapacitive and meminductive effects become dominant.